Heterosis studies based upon Mori CMS system in Brassica juncea L - Raju Ram Choudhary,; RK Sheoran,; Ram Avtar,; Deepak Kumar,; Samita, (Journal of Oilseed Brassica, 2026)
In present study Line x tester analysis was carried out to estimate all three types of heterosis (relative heterosis,heterobeltiosis and economic heterosis) for identification of superior cross combinations of Indian mustard [Brassicajuncea (L.) Czern. & Coss.]. Fifty hybrids along with 10 Mori CMS lines, 5 testers and check DMH-1 planted at OilseedsResearch Area, Department of Genetics & Plant Breeding, CCS Haryana Agricultural University, Hisar India during 2018-19 were evaluated for twelve characters including days to 50 % flowering, days to maturity, plant height (cm), number ofprimary branches per plant, number of secondary branches per plant, main shoot length (cm), number of siliquae on mainshoot, siliquae length (cm), number of seeds per siliquae, 1000-seed weight (g), oil content (%) and seed yield per plant(g). Analysis of variance revealed that sufficient genetic variability present among parents and crosses for all of thetraits. The results indicated presence of significantly high heterosis in desirable direction for all the characters exceptplant height (negative relative heterosis) and number of secondary branches/ number of seeds for per siliquae (economicheterosis). Two hybrids namely MA-9301 x MR-44 (12.85%) and MA-8701 x MR-38 (12.41%) showed significantpositive economic heterosis over standard check DMH-1. These hybrids were identified as superior hybrids for theirlarge-scale testing.